The effects of medicinal and food homologous substances on blood lipid and blood glucose levels and liver function in patients with nonalcoholic fatty liver disease: a systematic review of randomized controlled trials - Qian Zhang; Yatian Jia; Yuexing Zhang; Yan Wang; Xinru Li; Xiaoying Tian; Shifan Han (Lipids in Health and Disease, 2023)
Abstract Background Nonalcoholic fatty liver disease (NAFLD) is a prevalent chronic liver disorder worldwide. According to several previous studies, the treatment of patients with NAFLD using medicinal and food-homologous substances has consistent effects on the levels of blood lipids and blood glucose and liver function. Objective This systematic review was conducted to investigate the impact of medicinal and food homologous substances on blood lipid and glucose levels as well as liver function in patients with NAFLD. Methods A thorough search was conducted in eight databases, including China Science and Technology Journal Database (VIP), Chinese National Knowledge Infrastructure(CNKI), China Biomedical Literature Database (SinoMed), Wanfang Database, PubMed, Cochrane Library, Web of Science and Embase, for articles published from database inception until June 24, 2023. The methodological quality of the included studies was evaluated utilizing Cochrane Randomized Trial Risk Bias Tool, Edition 2 and GRADE methodology for assessment. Results A total of 13 randomized controlled trials, involving 829 patients with NAFLD, were included in the analysis, these studies included a total of 9 medicinal and food homologous substances. In the 13 studies, hawthorn (2), sea buckthorn (1), ginger (2), turmeric (4) (1 with chicory seeds), cinnamon (1), cardamom (1), purslane (1) and saffron (1) were included. The results of the included studies showed that medicinal and food homologous substances could improve high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), total cholesterol (TC), triglycerides (TGs), fasting blood glucose (FBG) and liver enzyme levels in patients with NAFLD to a certain extent, but the effect of turmeric on TC, liver enzyme levels is controversial. Conclusion In patients with NAFLD, dietary intervention using medicinal and food homologous substances can ameliorate blood lipid and blood glucose levels and liver enzymes to some extent. In clinical work, medicinal and food homologous substances can be used to provide patients with NAFLD with a safe and effective dietary plan to help prevent and treat disease onset and progression.